Synthesis and biological evaluation of novel 2‐arylquinoline‐3‐fused thiazolo[2, 3‐c]1, 2, 4‐triazole heterocycles as potential antiproliferative and antimicrobial agents. (17th February 2022) - Dhanavath, Ramulu; Dharavath, Ravinder; Kothula, Devender; Bitla, Sampath; Yaku, Gugulothu; Birdaraju, Saritha; Puchakayala, Muralidhar Reddy; Atcha, Krishnam Raju
Abstract: A series of novel 2‐arylquinoline‐3‐fused thiazolo[2, 3‐c]1, 2, 4‐triazole heterocycles 9a‐t were efficiently synthesized using simple conventional methods in good yields. The structure of newly synthesized molecules was characterized on the basis of their IR, 1 H NMR, 13 C NMR and mass spectral data. Among 9a‐t, compounds 9h, 9n, 9b and 9d exhibited highly significant antiproliferative activity against two cancer cell lines C6 (nerve cells) and MCF‐7 (human breast adenocarcinoma cells) when compared with standard reference Doxorubicin . In vitro antimicrobial activities of target compounds 9h, 9b, 9d, 9m and 9n were effectuated on Gram‐positive Staphylococcus aurus (ATCC 25923), Bacillus subtilis (ATCC 6633) and Gram‐negative strains Klebsiella Pneumonia (ATCC 31488) and Escherichia coli (ATCC 25966) strains and found to exhibit promising activity against standard Ciprofloxacin drug. Further, when in vitro antifungal activity was conducted on Aspergillus flavus and Aspergillus niger strains 9h, 9b, 9d and 9n were exhibited potent activity when compared with standard Fluconazole drug moiety. Abstract :